2023
DOI: 10.3389/fpls.2023.1169310
|View full text |Cite
|
Sign up to set email alerts
|

Interplant carbon and nitrogen transfers mediated by common arbuscular mycorrhizal networks: beneficial pathways for system functionality

Abstract: Arbuscular mycorrhizal fungi (AMF) are ubiquitous in soil and form nutritional symbioses with ~80% of vascular plant species, which significantly impact global carbon (C) and nitrogen (N) biogeochemical cycles. Roots of plant individuals are interconnected by AMF hyphae to form common AM networks (CAMNs), which provide pathways for the transfer of C and N from one plant to another, promoting plant coexistence and biodiversity. Despite that stable isotope methodologies (13C, 14C and 15N tracer techniques) have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 150 publications
0
2
0
Order By: Relevance
“…The authors strive to elucidate the functionality of these transitions and their implications for plant cohabitation, species diversity, and community stability. Their findings demonstrate that CAMNs significantly influence one-way changes in C and N, ranging from 0.02% to 41% for C and 0.04% to 80% for N [33]. C and N transition through CAMNs significantly affect plant functionality and biodiversity.…”
Section: The Impact Of Amf On Nitrogen Acquisition and Allocationmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors strive to elucidate the functionality of these transitions and their implications for plant cohabitation, species diversity, and community stability. Their findings demonstrate that CAMNs significantly influence one-way changes in C and N, ranging from 0.02% to 41% for C and 0.04% to 80% for N [33]. C and N transition through CAMNs significantly affect plant functionality and biodiversity.…”
Section: The Impact Of Amf On Nitrogen Acquisition and Allocationmentioning
confidence: 99%
“…Furthermore, the transfer of C and N through CAMNs has implications for species diversity. They [33] observed that higher levels of resource sharing lead to increased species richness within communities. This is because plants with lower resource availability can benefit from those with higher availability through these interplant transfers.…”
Section: The Impact Of Amf On Nitrogen Acquisition and Allocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is not surprising why AMF species are profoundly located in plants found in arid and desert climates ( Gollotte et al, 2004 , Ma et al, 2022a ). However, helping plants with water or providing C sources to fungi is an oversimplification of the structure–function correlation with respect to host interactions ( Luo et al, 2023 , Newsham et al, 1995 ). The AMF forms meristic structures that have distinct symbiotic functions within the cortex of the root, extending into the soil.…”
Section: Overview Of Amfmentioning
confidence: 99%
“…By extension, it has been widely hypothesized that the multi-plant-fungal relationships form "common mycorrhizal networks" (CMNs) which facilitate carbon and nutrient transfer between organisms, beyond the immediate plant-fungus mutualism formed by individuals. This relationship is often simplified to the mutual exchange of carbon-based photosynthates for limiting soil nutrients that are more readily bioavailable to fungi [5], but is known to exist along a continuum from parasitic to mutualistic [6][7][8][9]. A synthesis of empirical research at macro-and micro-levels of ecological organization reveals a gap in understanding of structural and functional properties that could predict how carbon and nutrients are transferred between plants through fungi in CMNs [10].…”
Section: Introductionmentioning
confidence: 99%